A case of adrenal metastasis of hepatocellular carcinoma diagnosed by endoscopic ultrasound‐guided fine‐needle aspiration - Tsuyoshi Ueda; Shinji Oe; Akitoshi Yoneda; Yudai Koya; Satoru Nebuya; Koichiro Miyagawa; Yuichi Honma; Michihiko Shibata; Shohei Shimajiri; Masaru Harada (DEN Open)
Abstract An 82‐year‐old man had been treated for lung adenocarcinoma and hepatocellular carcinoma (HCC). Contrast‐enhanced computed tomography examination showed swelling of the left adrenal gland, suggesting metastasis of lung adenocarcinoma, HCC, or primary adrenal tumor. Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) was performed for the pathological diagnosis, and adrenal metastasis of HCC was diagnosed. No notable complications due to EUS‐FNA were found. There have been reports of adrenal metastasis due to various cancers, but there are few reports that can confirm the diagnosis of adrenal metastasis of HCC using EUS‐FNA. Adrenal metastasis of HCC is not a rare condition, but it may be difficult to diagnose in the case of multiple cancer complications. We experienced a case in which EUS‐FNA was useful for the diagnosis of adrenal metastasis of HCC.